2015
DOI: 10.3906/tar-1406-171
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of banana (Musa balbisiana) basedon next-generation sequencing technology

Abstract: Banana (Musa spp.) is an important tropical fruit with high commercial potential. Musa balbisiana (B genome) is a progenitor of one of the most cultivated banana species and exhibits unique traits, including resistance or tolerance to many biotic and abiotic stresses. RNA sequencing of the Musa B genome would provide a vast array of transcriptomic information that could lead to the development of trait-specific markers and the discovery of new genes and regulatory sequences involved in resistance mechanisms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Furthermore, transcriptomics has been implemented in studies on Musa spp. (e.g., Backiyarani et al, 2015) enhancing our knowledge on physiological processes such as the fruit ripening (Asif et al, 2014) and the responses to abiotic stresses such as low-temperature (Yang Q. S. et al, 2015). This “-omics” has been largely used to study the interaction between BCAs, plant and/or microbiome, but no studies are available on the banana/ Foc pathosystem.…”
Section: Gaps In the Knowledge And Concluding Remarksmentioning
confidence: 99%
“…Furthermore, transcriptomics has been implemented in studies on Musa spp. (e.g., Backiyarani et al, 2015) enhancing our knowledge on physiological processes such as the fruit ripening (Asif et al, 2014) and the responses to abiotic stresses such as low-temperature (Yang Q. S. et al, 2015). This “-omics” has been largely used to study the interaction between BCAs, plant and/or microbiome, but no studies are available on the banana/ Foc pathosystem.…”
Section: Gaps In the Knowledge And Concluding Remarksmentioning
confidence: 99%
“…Identi cation of candidate gene/s responsible for the trait parthenocarpy in Musa spp. is a prerequisitefor the commercial exploitation of accessions with B genome that exhibit resistance against biotic or abiotic stresses 41 . It was reported that the trait parthenocarpy in banana is governed by three independent complementary geneswhere seediness could result even with the loss of one dominant gene 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a whole transcriptome from different tissues like leaf, root, sheath, flower bud, flower bract, pulp, and rhizome was performed by Backiyarani [12]. The identification of rapid activation and selective induction of cold tolerance genes ICE1 and MYBS3 and their pathways in plantain and banana, along with expression of other cold-specific genes provided useful information on the expression patterns using comparative transcriptomics [13].…”
Section: Short Commentarymentioning
confidence: 99%
“…Its application in Musa could improve our understanding of the molecular mechanisms involved in defence [14], biosynthesis, and other biochemical processes [12,13,15] providing a potential resource for future genetic or genomic studies on this important food crop. It can also be expected to bridge a critical gap that exists in the Musa comparative genomics and could ultimately contribute to the evolutionary and functional studies of its genes and genomes.…”
Section: Short Commentarymentioning
confidence: 99%